CONTRIBUTION OF PAYMENT SYSTEMS RESIDENTS IN RT 8/2 JOGLO USING VISUAL BASIC 6.0 - Syafran Zuldi; Syahril, SKom Syahril, SKom (Jurnal Sistem Informasi, 2005)
Writing is about dues payment system, residents in RT 2.8 Joglo, then it is expectedthat these systems can provide information quickly and efficiently and is useful forpeople who need the data and so on to more practical in providing a reliable andaccurate information. In payment of dues citizens here the author gives residentsconvenience to pay dues on each citizen.With the display system contribution payment Joglo residents in RT 8.2 is expectedin the payment of resident tuition will be easier and faster presentation.